Air mass history linked to the development of Arctic mixed-phase clouds - Murray-Watson,R; Gryspeerdt,E (2025)
The development of clouds during marine cold-air outbreaks (MCAOs) represent a complex phenomenon, transitioning from stratocumulus decks near ice edges to cumuliform fields downwind. This change cloud morphology changes the radiative properties of the cloud, and therefore is of importance to the surface energy budget. Therefore, it is crucial to understand the factors which may drive transition to a broken cloud field. Previous in situ and modelling studies suggest the formation of ice may enhance precipitation and therefore accelerate break-up. However, little is known about the development of mixed-phase clouds in MCAOs. This study uses pseudo-Lagrangian trajectories and satellite data to analyze this mixed-phase cloud development. We observe a rapid transition from liquid to ice phases in MCAO clouds, contrasting with similar cloud formations outside MCAO conditions. These mixed-phase clouds initially form at temperatures below -20°C near ice edges but can dominate even at -13°C further into outbreaks. This temperature shift suggests a significant role for biological ice nucleating particles (INPs), which increase in prevalence as air masses age over marine environments. The study also notes the influence of the air mass's history over snow- and ice-covered surfaces, which may be low in INPs, on cloud evolution. This link helps explain seasonal variations in Arctic cloud development, both during and outside of MCAOs. Our findings emphasize the importance of understanding local marine aerosol sources and the broader INP distribution in the Arctic for accurate cloud phase modeling in the region.